2018
DOI: 10.1093/mnras/sty2185
|View full text |Cite
|
Sign up to set email alerts
|

AGN feedback in the Phoenix cluster

Abstract: Active galactic nuclei (AGN) release a huge amount of energy into the intracluster medium (ICM) with the consequence of offsetting cooling and star formation (AGN feedback) in the centers of cool core clusters. The Phoenix cluster is among the most massive clusters of galaxies known in the Universe. It hosts a powerful starburst of several hundreds of Solar masses per year and a large amount of molecular gas in the center. In this work we use the high-resolution Reflection Grating Spectrometer (RGS) on board X… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 48 publications
6
23
0
Order By: Relevance
“…However, they also showed that the cooling rates may still be high enough to explain the H α luminosity and the star formation rates measured with the Hubble Space Telescope and WISE. Pinto et al () have shown that the cooling rate of 350 ± 130 M ⊙ yr −1 below 2 keV measured with RGS in the Phoenix cluster is consistent with the star formation rate in this object and is high enough to produce the molecular gas found with ALMA in the filaments via instabilities during the buoyant rising time (Russell et al ).…”
Section: Rgs Synergiessupporting
confidence: 55%
See 1 more Smart Citation
“…However, they also showed that the cooling rates may still be high enough to explain the H α luminosity and the star formation rates measured with the Hubble Space Telescope and WISE. Pinto et al () have shown that the cooling rate of 350 ± 130 M ⊙ yr −1 below 2 keV measured with RGS in the Phoenix cluster is consistent with the star formation rate in this object and is high enough to produce the molecular gas found with ALMA in the filaments via instabilities during the buoyant rising time (Russell et al ).…”
Section: Rgs Synergiessupporting
confidence: 55%
“…This indicates that turbulence contributes to the total energy for less than ∼5% and is consistent with the measurements of Hitomi for Perseus (Hitomi Collaboration ). Bambic et al () and Pinto et al () expanded this argument and showed that the propagation velocity is too low to achieve a balance between gas cooling and heating via dissipation of turbulence (Figure ), previously invoked by Zhuravleva et al () using surface brightness fluctuations. An additional source of heating may be sound waves (Fabian et al ).…”
Section: Rgs's Unique Contributionsmentioning
confidence: 94%
“…At small radii (r < 10 kpc), the profile dips down to ∼800 M yr −1 , which is a relatively small change compared to the 2-3 orders of magnitude that most clusters decline at similar radii. We compare this profile to estimates of the cooling rate from XMM RGS spectroscopy (Pinto et al 2018). Based on Figure 8, we estimate that the cooling from 2 → 0 keV is localized to r < 12 kpc, and that the gas cooling from 4 → 2 keV is in a shell at 12 < r < 20 kpc.…”
Section: Discussion 41 Cooling Flows Star Formation and Mixingmentioning
confidence: 96%
“…Red points and the shaded red curve show the cooling rate profile for the Phoenix cluster, which is significantly flatter than the median cool core profile, with a central cooling rate elevated by a factor of ∼10 3 above the typical low-z cluster. Blue shaded regions show the XMM-RGS spectroscopic cooling rates from Pinto et al (2018), where we have converted temperature bins into radial bins using the three-dimensional temperature profile from Figure 8. These data further support the picture in which cooling is proceeding with relatively little impedance at the center of the Phoenix cluster.…”
Section: Discussion 41 Cooling Flows Star Formation and Mixingmentioning
confidence: 99%
“…Simulations of the X‐ray spectrum of the Phoenix cluster ( z = 0.59) based on XMM‐Newton RGS (Pinto et al ) for the X‐ray integral field unit and Resolve spectrometers. The integration time is 25 and 250 ks, respectively.…”
Section: Breakthroughs Expected From Athena On the Astrophysics Of Exmentioning
confidence: 99%